Integration of Social Entrepreneurship and Supply Chain Management - Maksimova Svetlana Mikhailovna; Kuzminykh Svetlana Sergeevna (International Journal of Supply Chain Management, 2020)
Abstract— The purpose of this paper is to present a framework for pursuing global entrepreneurship where supply chain management can often serve as a platform for resource acquisition, market development, and risk mitigation. In this research the organizational and economic features of the development and implementation of integrated supply chain and social entrepreneurship projects studied. Then the specifics of the requests and needs of the target audience in entrepreneurship projects determined by taken it to develop a value chain for festival participants, an organizational structure for project management. The practical result of the study showed that supply chain management had moderating role effected positively by corporate entrepreneurship to business performance.